The focus group guidebook - Morgan, David L.; Krueger, Richard A.; King, Jean A. (Thousand Oaks, Calif. ; London : SAGE, 1998)
"Providing a general introduction to focus group research, The Focus Group Guidebook includes the appropriate reasons for using focus groups and what you can expect to accomplish with them. It provides a brief history of focus groups, a discussion of when to use focus groups and why, and several brief case studies illustrating different uses of focus groups. Author David L. Morgan also extensively provides the timeline and costs associated with focus groups, including a discussion of the ethical issues involved in focus group research. Thoroughly covering all the information to help you start your focus group project, this guidebook is appropriate for anybody beginning a focus group, as well as managers or clients who will be using focus groups."--BOOK JACKET.
Keywords: Focus groups